Association Between Percent Body Fat Reduction and Changes of the Metabolic Score for Insulin Resistance in Overweight/Obese People with Metabolic Dysfunction-Associated Steatotic Liver Disease - Han Y; Liu J; Li W; Zhang F; Mao Y (Diabetes, Metabolic Syndrome and Obesity)
Yan Han,1,2,* Jinhan Liu,2,3,* Wenjian Li,4 Fan Zhang,1,2 Yonghua Mao1,5 1Department of Endocrinology, Changzhou Third People’s Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, People’s Republic of China; 2Department of Clinical Nutrition, Changzhou Third People’s Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, People’s Republic of China; 3Department of Liver Diseases, Changzhou Third People’s Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, People’s Republic of China; 4Department of Urology, Changzhou Third People’s Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, People’s Republic of China; 5Department of Nursing, Changzhou Third People’s Hospital, Changzhou Medical Center, Nanjing Medical University, Changzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fan Zhang; Yonghua Mao, Department of Endocrinology, Changzhou Third People’s Hospital, Changzhou Medical Center, Nanjing Medical University, 300 Lanling North Road, Changzhou, Jiangsu, 213001, People’s Republic of China, Tel +86-0519-82008311, Email yifan52518@163.com; symyh2103@163.comPurpose: This study investigated the relationship between the difference in percent body fat (∆PBF) decrease and the change in the metabolic score for insulin resistance (METS-IR) in Chinese overweight/obese people with combined metabolic dysfunction-associated steatotic liver disease (MASLD) after weight loss.Patients and Methods: A total of 357 overweight/obese MASLD patients were included using a retrospective study method. The subjects were divided into two groups (< 5% and ≥ 5%) based on the ∆PBF. The changes in METS-IR (∆METS-IR) and metabolic indices before and after fat loss were compared between the two groups. Spearman correlation analysis was employed to investigate the correlation between METS-IR changes and the decrease in PBF. A linear regression model was fitted using a restricted cubic spline (RCS) curve to investigate the dynamic relationship between ∆METS-IR and ∆PBF.Results: Following the fat reduction, both groups’ body measurements and liver fat content exhibited a notable reduction, accompanied by a decline in METS-IR. In particular, the decrease in METS-IR was more pronounced in the group with a ≥ 5% decrease in PBF. Significant correlations were observed between ∆PBF and various insulin resistance indices. The correlation between ΔPBF and ∆METS-IR was noteworthy (r = 0.438, p < 0.001). RCS analysis revealed that when ΔPBF exceeded 3.2%, ∆METS-IR exhibited an upward trend with further reduction in PBF.Conclusion: The reduction of PBF was closely associated with changes in METS-IR, indicating that fat loss is an effective method for improving insulin resistance in overweight/obese MASLD patients.Keywords: metabolic dysfunction-associated steatotic liver disease, insulin resistance, metabolic score for insulin resistance, triglyceride-glucose index